The contributions of public policies for strengthening family farming and increasing food security: The case of Brazil. (March 2019) - Berchin, Issa Ibrahim; Nunes, Nei Antonio; de Amorim, Wellyngton Silva; Alves Zimmer, Gabriel Alfredo; da Silva, Franciani Rodrigues; Fornasari, Vitória Haendchen; Sima, Mihaela; de Andrade Guerra, José Baltazar Salgueirinho Osório
Highlights: Food security is a major global challenge of the XXI st century. Good governance is a key player in reducing poverty and increasing food security. Family farming, complementary to large-scale farming, is crucial to global food security. Abstract: Ensuring food security is one of the main challenges of the 21st century in developing countries. The aim of this study is to analyze how public policies contribute to the strengthening of family farming in order to increase the food security. The study encompasses a literature review of the relations between public policies, family farming and food security and relates them with a review of the main policy framework in Brazil. The results show that the Brazilian policy framework in terms of strategies to strengthen food security is intrinsically focused on family farming and, in fact, these policies contribute to enhancing food security. Thus, family farming, in conjunction with large-scale farming, is crucial to Brazilian and global food security. Even though there are some scientific publications on food security and official reports on the subjects in Brazil, little has been written about family farming as a strategy for public policies to enhance food security in Brazil. Therefore, this paper can potentially contribute to the literature on good governance in terms of agriculture and food security policies by presenting the well succeeded case of Brazil since the early 2000s.